The results of long-term growth hormone replacement therapy in Turkish children with growth hormone deficiency - Yordam, Nurşen; Kandemir, Nurgün; Alikaşifoğlu, Ayfer (The Turkish Journal of Pediatrics, 1998)
From a total of 118 patients treated for growth hormone deficiency, 37 (23 boys, 14 girls) have reached their final height. Twenty-five patients had isolated growth hormone deficiency (IGHD) and 12 had multiple pituitary hormone deficiency (MPHD). Growth hormone deficiency was diagnosed and treated late in both boys and girls. The mean height standard deviation score (SDS) for chronological age (CA) increased significantly from -4.43 to -1.94 during the therapy. The target height was not achieved in boys or girls nor in MPHD and IGHD groups, although they have reached the third percentile of the normal Turkish population. The height and chronological age of the patients at the start of the treatment correlated significantly with final height in all patients. Therefore, early diagnosis and treatment is important to complete catch-up growth in growth hormone deficient patients. The height prognosis is improved with administration of a recombinant form of human growth hormone (GH) as daily subcutaneous injections with a dose of 0.1 IU/kg, when compared to the earlier studies with pituitary GH.
Keywords: growth hormone deficiency; final height; growth hormone treatment